Improving Vocabulary Mastery of Junior High School Students by Watching Digital Storytelling - Septian Dwi Anggara (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2023)
Learning vocabulary becomes one of the challenges in language learning. Choosing the right media will help the student to gain new words. Utilizing stories uploaded into digital applications in learning vocabulary can be helpful. This study aims to seek whether Voicethread as the media delivering story improves vocabulary mastery of junior high school students and to find students’ perception of digital storytelling to improve vocabulary mastery. This research is experimental research using quantitative descriptive methods.  There are pre-test and post-test to seek the increasing number of new vocabulary. Also, there is a questionnaire to find the students’ perception of using Voicethread in vocabulary learning. The result of the study reveals that students’ vocabulary increased. The students give positive responses to the use of digital storytelling and recommend using digital storytelling in vocabulary learning. The result also indicates that digital storytelling influences motivation to study independently.